[PP.19.01] THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA (ARCADIA-POL STUDY) – EVALUATION OF BLOOD PRESSURE PROFILE AND SUBCLINICAL TARGET ORGAN DAMAGE IN PATIENTS WITH RENAL FMD. (September 2017) - Warchol-Celinska, E.; Hanus, K.; Miadziolko, M.; Januszewicz, M.; Florczak, E.; Michalowska, I.; Dobrowolski, P.; Witowicz, H.; Stryczynski, L.; Prejbisz, A.; Paschalis-purtak, K.; Pucilowska, B.; et al.
Abstract : Objective: To evaluate blood pressure (BP) profile and subclinical target organ damage in patients with renal fibromuscular dysplasia (FMD) enrolled into the ARCADIA-POL study. Design and method: From 144 patients with FMD in any vascular bed enrolled in the ARCADIA-POL study in 2015, we analyzed 127 patients (104F, 23 M, mean age:44.8 ± 15.9 years, range:18–75) with confirmed renal FMD. All patients underwent detailed clinical evaluation including office blood pressure (BP) levels, ABPM, biochemical evaluation, biobanking, duplex Doppler of cervical and abdominal arteries and whole body angio-CT. In all patients left ventricular hypertrophy (LVH) was evaluated in echocardiography according to the current 2013 ESH/ESC guidelines. In parallel as a reference group we also evaluated 62 patients with essential hypertension (EHT) (43F, 19 M, mean age: 48.3 ± 11.1 years) matched in regards to gender, body mass index, glycemic status, BP levels and number of medication (p > 0.05). Results: When comparing 127 patients with FMD to the matched group of patients with EHT we observed no significant differences in office and ambulatory BP levels. The prevalence of resistant hypertension (RHT) and true RHT did not differ between patients with FMD and EHT (16.5% vs 13.8%, p = 0.65; 12.6% vs. 8.2%, p = 0.37). There was also no difference in regards to the dipping status between both groups. We also evaluated the subclinical target organ damage in both groups. There were no differences in the prevalence of LVH between the groups (38.4% vs. 35.1%, p = 0.72) as well as between the parameters assessing systolic and diastolic LV function. Both groups did not also differ in intima-media thickness, estimated glomerular filtration ratio and albuminuria as well as resistive and pulsatility indexes assessed in duplex Doppler. After excluding patients with the presence of significant renal artery stenosis from the group with renal FMD the results remained still non-significant. Conclusions: Our results indicate that patients with FMD included into ARCADIA-POL study did not differ from patients with essential hypertension in respect to blood pressure profile and intensity of subclinical target organ damage.